The Languages of Multinormativity - Gunnar Folke Schuppert (Rechtsgeschichte – Legal History, 2017)
When speaking of multinormativity, a range of different regulatory regimes and, beyond this, diverse worlds of rules are envisaged. One can only get a hold of these complex phenomena if one looks at them from the perspective of different disciplines and is open to devote oneself to the different languages and vocabularies of these disciplines. Therefore, it is quite plausible to speak of multiple »languages of normativity« when describing and analysing multinormativity. The article attempts this.
Keywords: 330; fragmentation of the legal system; decoupling the state and law; law as group privileges; parallel orders; governance of diversity